Representation of Islamic Poetry in Kuntulan Purwakarta: Semiotic Approach - Dinda Dwi Pratiwi; Yulianeta Yulianeta; Tedi Permadi (Wacana : Jurnal Bahasa, Seni, dan Pengajaran, 2026)
Kuntulan is a traditional performing art that has developed within pesantren communities in Purwakarta, characterized by a unique combination of martial arts, traditional music, and Arabic-language sholawat (Islamic chants). This study employs a descriptive qualitative method, focusing on analyzing the sholawat lyrics in Kuntulan using Charles Sanders Peirce’s semiotic theory and Stuart Hall’s representation theory to explore Islamic values. The study identifies various religious signs and the meanings of Islamic teachings in the context of local culture. The findings reveal that the lyrics convey Islamic values such as love for the Prophet, intercession, and monotheism, and also represent the religious identity of the pesantren community in a performative and emotional way. Furthermore, the analysis shows that these lyrics function as part of an oral tradition that effectively transmits values, shapes moral character, and strengthens collective spirituality in a continuous and aesthetic manner.